Hadith #3075 - Sunan Abi Dawud - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Abdullah bin Mubarak عبد الله بن المبارك; Ahmed bin Abd'h al-Aamly أحمد بن عبدة الآملي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Ibn Ishaq through a different chain of narrators and to the same effect. Instead of the phrase “one who transmitted this tradition to me” this version has “A man from among the Companions of the Prophet (ﷺ) and probably he was Abu Sa’id Al Khudri. I saw the man striking at the roots of the palm trees.”
Grade: Hasan